Photo‐crosslinked poly(ethylene glycol) diacrylate (PEGDA) hydrogels from low molecular weight prepolymer: Swelling and permeation studies. Issue 2 (12th September 2016) - Cavallo, Anna; Madaghiele, Marta; Masullo, Ugo; Lionetto, Maria Giulia; Sannino, Alessandro
ABSTRACT: The aim of this work was to assess the diffusive properties of poly(ethylene glycol) diacrylate (PEGDA)‐based hydrogels, derived from low MW prepolymers, in view of potential biomedical applications. Several hydrogels were synthesized through UV irradiation of PEGDA solutions for different exposure times. Swelling measurements in distilled water were performed to estimate the yielded crosslink density, while swelling tests at 37 °C in selected media allowed to analyze the mesh size changes induced by various pH and ionic strength (IonS) conditions. The transport of glucose and insulin through thin hydrogel membranes was finally assessed in a modified Ussing chamber at physiological values of pH and IonS (7.4 and 150 mM, respectively). Results showed that the swelling was dependent on the IonS (with swelling reductions up to 20–30% for IonS increases in the range 0–300 mM) and, to a lesser extent, on the pH of the surrounding medium (with swelling increments of about 10% for increasing pH in the range 2.5–11). All hydrogels were also permeable to glucose and insulin, which displayed comparable diffusion coefficients (in the order of 10 −6 cm 2 /s). Specific interactions between glucose and the polymer chains were evidenced by values of the partition coefficient higher than unity. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44380. Abstract :